Phonetic and Morphological Deviation in Socotra: Causes and Remedies: - Salah Naji Muhammad Ali; Ebrahim Qaid Saleh Alhabbari (Solo International Collaboration and Publication of Social Sciences and Humanities, 2025)
Objective: The objective of the current study was to reveal most prominent causes of    Socotri language and propose scientific and practical solutions. It explores the historical roots of Socotri as an ancient South Arabian language predating Classical Arabic and examines its relationship with Arabic linguistic structures. Theoretical framework: This study examines the phonological and morphological phenomena in Socotra, focusing on the reasons for its many deviations, which are due to the presence of an ancient South Arabian language whose roots extend back to the pre-Northern Arabic or Classical Arabic, and which still exists till today, and is used among the inhabitants of the island-Socotra. It also identifies possible solutions to them, based on the theories of phonetics and morphology, and the analysis of linguistic differences affected by historical, social, and environmental factors. Literature review: The review addresses previous studies on phonetic and morphological phenomena in Socotra, highlighting the contributions of scholars to this area. It also examines the theoretical foundations of these phenomena and their role in preserving them from deviations. Methods: The study adopts an inductive, analytical, and descriptive methodology, examining linguistic deviation in general, the relationship between the Socotri language and Arabic, and the phonetic and morphological deviations it contains, while presenting some proposals for addressing this phenomenon. Results: The results reveals that the difference in some sounds between Arabic and Socotra, the difference in some phonetic syllables, and the distribution of vowels in them are among the most important causes of phonetic and morphological deviation. Implications: The study's implications include language preservation, linguistic policy recommendations, and an enhanced understanding of Socotra’s linguistic diversity, contributing to broader discussions on aspects of languages and dialectology. Novelty: The novelty of this study lies in its focus on the most prominent areas of phonetic and morphological deviation in Socotra, a topic that has not been addressed in depth in previous studies.